Corporate Tax Aggressiveness and Managerial Capabilities: Insights From Indonesian Firms - Yudith Janurita Putu Kurniawati; Agus Fredy Maradonab (Green Publisher Indonesia, 2024)
This study aims to investigate the effect of management ability, business strategy, and profitability on corporate tax aggressiveness. This study uses mediation analysis with the Smart PLS approach on a sample of basic materials sector companies listed on the IDX from 2020 to 2022. The results show that more capable management tends to adopt a conservative approach in tax management practices. In addition, business strategies such as prospector and defender have a significant impact on tax aggressiveness. More profitable companies tend to implement more aggressive tax strategies. Companies need to improve managerial capabilities to manage taxes more effectively, as well as formulate appropriate business strategies to mitigate tax risks in the future. With a better understanding of tax risks, companies can minimize potential tax disputes and protect their reputation and long-term performance. This study extends the research time scope to 2022 and uses corporate governance mechanisms as moderating variables, both internal and external, which have not been widely studied in previous studies.